Refractive error, amblyopia and ocular alignment among schoolchildren in Saudi Arabia. - Alrasheed, Saif Hassan; Alhoshan, Saja A.; Alnasser, Bashair N. (Eastern Mediterranean Health Journal, 2026)
Background: Normal visual development starts early in childhood, and achieving optimal corrected visual acuity, binocular function and ocular alignment is key to healthy visual maturation. Aim: To assess the prevalence of refractive error, amblyopia and ocular alignment among school children in Qassim Region, Saudi Arabia. Methods: Using a modified refractive error study in school-aged children protocol, we collected data from 850 children aged 6-17 years from 6 randomly selected schools in Qassim, Saudi Arabia, between March and May 2024. We assessed refractive error with a noncycloplegic autorefractometer, ocular alignment with the alternate cover test and prism bar, and anterior/posterior segments using a slit-lamp and ophthalmoscopy. We analysed the data using SPSS version 25 and further analysed the prevalence of refractive error amblyopia and ocular misalignment using MedCalc for Windows. P < 0.05 was regarded as statistical significance. Results: The overall prevalence of refractive error was 61.1%, including hyperopia (30.5%), myopia (19.3%) and astigmatism (11.3%). M ost children (68.0%) had o rthophoria at near fixation. Phoria was found in 25.5% of children, predominantly exophoria (19.8%), while strabismus was present in 6.5%, mainly esotropia (4.8%). Ocular alignment status was significantly associated with age and gender (P < 0.001). Amblyopia affected 8.4% of the children, with higher prevalence in males (P = 0.034) but there was no significant association with age (P = 0.094). Children without previous eye examinations were at higher risk for developing amblyopia (odds ratio = 3.58, P < 0.001). Conclusion: The high prevalence of refractive error, amblyopia and strabismus in this study indicates an increased risk of visual disorder among the children. There is therefore a need for routine vision screening and improved access to paediatric eye care.